The contemporary role of renal mass biopsy in the management of small renal tumors - Lim, Amy; O'Neil, Brock; Heilbrun, Marta; Dechet, Christopher; Lowrance, William T. (Frontiers in Oncology, 2012)
The selective use of percutaneous biopsy for diagnosis in renal masses is a relatively uncommon approach when compared to the management of other solid neoplasms. With recent advancements in imaging techniques and their widespread use, the incidental discovery of asymptomatic, small renal masses (SRM) is on the rise and a substantial percentage of these SRM are benign. Recent advances in diagnostics have significantly improved accuracy rates of renal mass biopsy (RMB), making it a potentially powerful tool in the management of SRM. In this review, we will discuss the current management of SRM, problems with the traditional view of RMB, improvements in the diagnostic power of RMB, cost-effectiveness of RMB, and risks associated with RMB. RMB may offer important information enabling treating clinicians to better risk-stratify patients and ultimately provide a more personalized treatment approach for SRM.